The MOSDEF Survey: calibrating the relationship between H α star formation rate and radio continuum luminosity at 1.4 < z < 2.6. Issue 3 (22nd August 2020) - Duncan, Kenneth J; Shivaei, Irene; Shapley, Alice E; Reddy, Naveen A; Mobasher, Bahram; Coil, Alison L; Kriek, Mariska; Siana, Brian
ABSTRACT: The observed empirical relation between the star formation rates (SFR) of low-redshift galaxies and their radio continuum luminosity offers a potential means of measuring SFR in high-redshift galaxies that is unaffected by dust obscuration. In this study, we make the first test for redshift evolution in the SFR-radio continuum relation at high redshift using dust-corrected H α SFR. Our sample consists of 178 galaxies from the MOSFIRE Deep Evolution Field (MOSDEF) Survey at 1.4 < z < 2.6 with rest-frame optical spectroscopy and deep 1.5 GHz radio continuum observations from the Karl G. Jansky Very Large Array (VLA) GOODS North field. Using a stacking analysis, we compare the observed radio continuum luminosities with those predicted from the dust-corrected H α SFR assuming a range of z  ∼ 0 relations. We find no evidence for a systematic evolution with redshift, when stacking the radio continuum as a function of dust-corrected H α SFR and when stacking both optical spectroscopy and radio continuum as a function of stellar mass. We conclude that locally calibrated relations between SFR and radio continuum luminosity remain valid out to z  ∼ 2.